THE EFFECT OF THE PREDICT OBSERVE EXPLAIN (POE) LEARNING MODEL ON FACE-TO-FACE LEARNING (F2F) ON THE UNDERSTANDING OF SCIENCE CONCEPTS: IN THE FOURTH GRADE OF ELEMENTARY SCHOOL STUDENTS - Efrillita Sampurno; Fitria Wulandari (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2023)
The purpose of this research to find out the effect and how much influence thelearning model had on predicting and learning the effect of face-to-facelearning on understanding science concepts. This research method usesquantitative experiments a type of the study Quasi Experimental Design andthe form design used is a nonequivalent control group design. The resultsindicated that hypotheses should be tested and problem statements answered,the analysis data techniques use were the Independent Sample T Test and theN-Gain test. You can tell by looking at the average when given treatment usedthe learning model POE in the Post-test to get an average value of 76.49 forthe experimental class and 61.36 for the control class. From the results of theIndependent Samples T Test post-test scores for the experimental and controlclass, namely 2.721 > 1.67 then, H0 is reject and H1 is accept, indicated thatthere is an influence and results of NGain experimental class give POE modelindicated that is a big influence so that it can be use as a learning model. Theconclusion in this study is it learning model POE in face-to-face learning ispositive and significant effect understand concepts science for fourth gradeelementary school student, so that it can be used as a solution in learningscience at elementary school.